Characteristics of online treatment seekers interested in a text messaging intervention for problem drinking: adults 51 and older versus middle-aged and younger adults - Kuerbis, Alexis (Ment Health Addict Res, 2017)
According to the Institute of Medicine, the vast older adult population is estimated to have mental health and substance use disorders at unprecedented rates and will place high demand on an unprepared healthcare system. Online and mobile health interventions, such as text messaging, could provide an alternative form of frontline intervention that could alleviate some of the burden on the healthcare system; however, it remains unknown what are characteristics of adults over 50 who might be interested in a mobile health behavioral intervention and how they may differ from their younger counterparts. To explore the characteristics of those interested in a text messaging intervention by age, we examined screening data for a randomized controlled trial testing a text messaging intervention to reduce drinking among 1,128 hazardous and problem drinkers, aged 21–30, 31–50, and 51 and older. Participants were recruited online through website advertising on alcoholscreening.org and moderationmanagement.org. Results demonstrated that over a quarter of individuals pursuing online and/or text messaging treatment were 51 and older. These participants reported heavy drinking, with significantly greater number of days drinking and binge drinking than the younger groups, but with fewer consequences. Across age groups, a vast majority of participants were female. Findings demonstrate that a group of adult heavy drinkers 51 and older already pursue online treatment and are interested in using a text messaging intervention to help them reduce drinking, suggesting an avenue to engage this population using an alternative frontline treatment.